Early Diagnosis of Bilateral Supplemental Primary and Permanent Maxillary Lateral Incisors: A Case Report - Yildirim, Gozde; Bayrak, Sule (European Journal of Dentistry, 2011)
Supernumerary teeth occur frequently in permanent dentition, but they are rarely found in primary dentition. Supernumerary teeth of orthodox shape and size that resemble normal dentition are called ‘supplemental teeth’. Supplemental teeth are less common than supernumerary teeth and are often overlooked because of their normal shape and size. Supplemental teeth may cause esthetic problems, delayed eruption and crowding, and they require early diagnosis and treatment to prevent complications. The case reported here is one of bilateral supplemental teeth impeding the eruption of permanent maxillary lateral incisors, and it emphasizes the importance of early diagnosis and treatment during early mixed dentition. (Eur J Dent 2011;5:215-219)
Keywords: Supernumerary teeth; Supplemental teeth; Lateral incisor